FULFILLING THE NEEDS OF THE ELDERLY TOWARDS THE QUALITY OF LIFE OF THE ELDERLY IN THE HEALTH CENTER AREA - Istiqomah Dwi Andari; Umriaty -; Riska Arsita Harnawati (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
The increasing age of the elderly experiences biological, physical, psychological and social changes. This change will impact all aspects of life, including health. This is because as you get older, the function of your body's organs will decrease, either due to natural factors or disease. Analytical survey research that tries to explore the influence of fulfilling the needs of the elderly on the quality of life of the elderly. The research method uses a cross sectional design. The needs of the elderly affect the quality of life of the elderly. It can be seen from the physical condition of the elderly that almost all of them experience quality physical condition. The psychological condition of the elderly is in good condition and of good quality. Conditions for elderly social interactions run well and are of good quality. The coverage of the elderly's social environment is very good for the quality of life of the elderly in the Community Health Center area with a sample size of 128 elderly. Research results The characteristics of the elderly in this study consisted of the majority of male respondents, 63 (65.8%) of the total 128 elderly respondents studied. There were several qualities of the elderly studied. The life of the elderly is seen from the physical condition of the elderly as many as 78 (60.9%), The quality of life of the elderly is seen from the psychological condition with the quality category being 102 (79.6%) elderly. There are several qualities of life for the elderly seen from the quality of the social interaction of the elderly as many as 108 elderly (84.3%), some of the quality of life of the elderly is seen from the quality of the social environment of the elderly as many as 96 (75%)